(untitled) (Fiep Bulletin - online, 2016)
Functional training is conquering its space in gyms and personalized way due to their application form and help people in their everyday functions. Childhood obesity has increased dramatically in all industrialized countries, where physical inactivity seems to contribute in the same way that high and unbalanced food intake The aim of this paper is to discuss this methodological possibility of work.